Improving the Understanding of Pelayangan Village Community about Contemporary Fiqh of Fasting and Praying through Community Religious Development - Afandi, Ahmad; Richadt Al Austin; Lukman Hakim; M Alif Fahlefi; Rahmat Raja Adila Rahman; Sulthani Mukhlis; Untung Prayitno (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
Pelayangan Village, located on the banks of the Batang Hari River, faces challenges in religious understanding, particularly regarding prayer and fasting. Many people experience confusion in understanding what breaks the fast, such as using certain drugs or physical actions that do not break the fast. In addition, several issues of ikhtilaf related to the pillars of prayer, including differences in movements and recitations that often confuse performing prayer correctly. STAI As-Sunnah's Community Service program provides assistance during Ramadan to improve the community's religious understanding. This activity involves religious guidance, including Qur'anic studies, flash pesantren, tahsin training, and delivering short lectures after tarawih prayers. Using participatory action research (PAR) methodology, this program succeeded in increasing religious knowledge, strengthening friendships, and improving community worship practices. The positive impact of this program can be seen in the community's enthusiasm for participating in various religious activities, especially during the month of Ramadan. The results of this service show that PAR-based religious assistance can effectively improve the quality of life and religious understanding in rural communities.